Inferior Turbinate Hypertrophy and SFAR-Defined Allergic Rhinitis in Chronic Suppurative Otitis Media: A Cross-Sectional Study at Ngoerah Hospital, Bali - Ni Luh Sartika Sari; Made Prani Windasari; Ni Made Pasmiati Setyaningsih (Sriwijaya Journal of Otorhinolaryngology, 2026)
Background: Allergic rhinitis (AR) is an IgE-mediated inflammatory disease of the nasal mucosa and a recognised risk factor for chronic suppurative otitis media (CSOM) through Eustachian tube dysfunction, yet Indonesian data on this comorbidity remain scarce. Objective: To characterise Score for Allergic Rhinitis (SFAR)-defined AR and its association with inferior turbinate hypertrophy among CSOM patients at a tertiary ENT referral centre in Bali. Methods: A descriptive cross-sectional study, reported in accordance with the STROBE statement, consecutively enrolled 26 CSOM patients attending the ENT outpatient clinic of Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, from November to December 2025. AR was screened using the validated SFAR questionnaire (cut-off ≥7). Data were analysed with Wilson 95% confidence intervals (CI), bivariate odds ratios (OR), multivariable logistic regression, and receiver-operating-characteristic (ROC) analysis. Results: SFAR-defined AR was identified in 17 patients (65.4%; 95% CI 46.2–80.6). Most were female (65.4%) and aged 30–39 years (26.9%). Predominant symptoms were sneezing (42.3%), rhinorrhoea (34.6%) and nasal obstruction (23.1%); house dust was the leading trigger (94.1%). Inferior turbinate hypertrophy (80.8%) was strongly associated with AR (OR 12.8; 95% CI 1.15–142.6; p=0.034), and the SFAR score discriminated turbinate hypertrophy with an area under the curve of 0.776 (95% CI 0.527–1.00). Conclusion: Comorbid AR is highly prevalent among CSOM patients. Routine SFAR screening, particularly when inferior turbinate hypertrophy is present, may enable earlier AR detection and more comprehensive middle-ear management in Indonesian ENT practice.